Communication across languages and cultures - A perspective of brand name translation from English to Chinese - Sang, J.; Zhang, Grace (John Benjamins Publishing Co., 2008)
Communication across languages and cultures is a markedly complex issue, and translation is more than just a careful linguistic transfer: it is a purposeful action designed to achieve the most effective result in a target group. Few studies have discussed the role of communicative intent in translation, and this paper is a small step towards filling the gap. The conceptual framework adopted in this study is Skopostheorie (Vermeer, 1989), a functionalist approach with an emphasis on communicative Skopos (purpose or aim), target texts and audiences. Using a method of contrastive comparison among effective, ineffective and controversial brand name translations from English to Mandarin Chinese, a systematic analysis is conducted regarding four translation strategies: phonetic appeal, suitable meaning, socio-cultural adaptation and consumer acceptance.The findings demonstrate that any effective communication strategy needs to be in accordance with the communicative purpose of achieving an optimal impact upon the target group, and a successfully translated brand name should function in a target culture as effectively as the original name in a source culture. They suggest that a function oriented approach, rather than a source-text oriented approach, holds the key for a successful outcome. If the translated name in Chinese achieves the expected effect among the Chinese consumers, then it is unimportant whether the meaning or the sound is sustained. The most important thing is that translated brand names suit the needs of Chinese consumers.This study is significant in that it challenges the traditional sound/meaningbased approach, and provides enriched understanding of the importance of achieving communicative purposes and optimal functional impact in a target group. The insights gained from this study add a vital conceptual dimension to the study of translation, and cross-cultural communication in general. In addition, the findings of this study may also provide practical assistance for an effective outcome in translation, and have pedagogical value in the teaching of translation. While the discussion in this study is based on Chinese data, the findings have implications for the translation of other languages.